Microscopic investigations and pharmacognostic techniques used for the standardization of leaf of Rhus succedanea var. Himalaica J. D. Hook. Issue 12 (20th August 2019) - Khan, Shafqat Ali; Barkatullah; Ibrar, Muhammad; Ullah, Sami
Abstract: Rhus succedanea is generally traded, distributed, and sold in the markets in its crude and raw form. This may have been mixed with adulterants, mismanaged by malpractices, and substituted with other closely related drugs having different effect. This study is therefore carried out to authenticate the plant through pharmacognostic evaluations including morphological microscopic and physio‐chemical features. Morphologically, the Rhus is a perennial small sized deciduous tree, locally, called as Rakhkal in Pashto and Kakarsingi in Urdu. The organoleptic evaluation showed that leaf had pleasant, aromatic odor, and astringent taste. Anatomy of the midrib has shown a typical dicot histological differentiation. The leaf was hypostomatic showing anomocytic stomata with average stomatal number 27.1 ± 7.2 and stomatal index 14 ± 3.63. The average vein islet, vein termination, and palisade ratios were 13.6 ± 3.04, 10.21 ± 1.92, and 6 ± 2.01, respectively. Leaf powder showed the existence of various types of tissues. Fluorescence study and percentage extractive values were also carried out. The phytochemical screening showed the presence of carbohydrates, protein, alkaloids, phenols, flavonoids, terpenoids, and anthraquinones, whereas tannins and fixed oil was not detected. Quantitatively highest number of alkaloids 16% and flavonoids 19% in leaf was detected. The above parameters, being reported to the first time for, and are significant toward establishing the microscopic and pharmacognostic standards for future identification and authentication of genuine herbal drug. Abstract : Microscopic and pharmacognostic investigations for the standardization of herbal drug Rhus succedanea . Anatomical and micromorphological characteristics of leaf might be useful in the definition of the specie investigated and is a good source of taxonomic information that can help the species and genera delimitation. Pharmacognostic techniques are potentially significant for the standardization of herbal drug R. succedanea leaf in comparison with its adulterant. The phytochemical screening showed types and amount of various types of phytoconstituents of the plant. Further advance study is recommended to isolate the important phytoconstituents, and its exact pharmacological effect should be determined.